The relationship between obesity-related H19DMR methylation and H19 and IGF2 gene expression on offspring growth and body composition - Argentato, Perla Pizzi; Marchesi, Jorge Augusto Petroli; Dejani, Naiara Naiana; Nakandakare, Patrícia Yury; Teles, Laísla de França da Silva; Batista, Lívia Patrícia Rodrigues; Leitão, Maria Paula Carvalho; Luzia, Liania Alves; Ramos, Ester Silveira; Rondó, Patricia Helen (Frontiers in Nutrition, 2023)
Background and objective: Imprinted genes are important for the offspring development. To assess the relationship between obesity-related H19DMR methylation and H19 and IGF2 gene expression and offspring growth and body composition. Methods: Thirty-nine overweight/obese and 25 normal weight pregnant women were selected from the “Araraquara Cohort Study” according to their pre-pregnancy BMI. Fetal growth and body composition and newborn growth were assessed, respectively, by ultrasound and anthropometry. The methylation of H19DMR in maternal blood, cord blood, maternal decidua and placental villi tissues was evaluated by methylation-sensitive restriction endonuclease qPCR, and H19 and IGF2 expression by relative real-time PCR quantification. Multiple linear regression models explored the associations of DNA methylation and gene expression with maternal, fetal, and newborn parameters. Results: H19DMR was less methylated in maternal blood of the overweight/obese group. There were associations of H19DMR methylation in cord blood with centiles of fetal biparietal diameter (BPD) and abdominal subcutaneous fat thickness and newborn head circumference (HC); H19DMR methylation in maternal decidua with fetal occipitofrontal diameter (OFD), HC, and length; H19DMR methylation in placental villi with fetal OFD, HC and abdominal subcutaneous fat thickness and with newborn HC. H19 expression in maternal decidua was associated with fetal BPD and femur length centiles and in placental villi with fetal OFD and subcutaneous arm fat. IGF2 expression in maternal decidua was associated with fetal BPD and in placental villi with fetal OFD. Conclusion: To our knowledge, this is the first study to demonstrate associations of imprinted genes variations at the maternal-fetal interface of the placenta and in cord blood with fetal body composition, supporting the involvement of epigenetic mechanisms in offspring growth and body composition.